MODERN APPROACH TO DETERMINING THE STRENGTH OF INTERACTION TRACK AND ROLLING STOCK IN THE ZONE OF SWITCHES - Danilenko, E. I.; Molchanov, V. M. (Science and Transport Progress, 2003)
The calculation technique of definition of forces of a track and rolling stock interaction is shown, the features of its use, calculation schemes are described. The problems arising at calculations of forces of a way and a rolling stock interaction in a tarnout zone and a ways of their resolving are considered.